“Mom, I Want to Be a Youtuber”: an Unregulated Reality - Durán Alonso, Silvia (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The objective of this study is to determine the legal regime of the activity of minors as content creators on YouTube. The duty of their parents to intervene in said activity, and of the platforms themselves, which should exercise greater control, to avoid risks for minors derived from their overexposure, will also be examined. Likewise, it is also necessary to regulate the control of the economic benefits that the activities of minors on the Internet may imply, as well as the duties of parents in terms of supervising.